Taxonomic and distributional assessments of Chaerephon plicatus (Chiroptera: Molossidae) from Vietnam - Thong, Vu Dinh (Academia Journal of Biology, 2015)
To date, Wrinkle-lipped Bat (Chaerephon plicatus) is the only species of the family Molossidae in Vietnam. It is found throughout much of Asia but rarely recorded in the country. Every published record of this species from Vietnam was only resulted from a single individual with little data on morphology. Particularly, the previous publications did not include any information about either colony size or roosting site of the species within Vietnam. Between 2001 and 2014, a series of field surveys was conducted throughout the country with an intensive search for free-tailed bat species. The obtained results indicate that Wrinkle-lipped Bat is a widespread bat species but its known roosting sites in Vietnam are quite distjunct. Its colony size is in both seasonal and geographical variations ranging from several hundreds to over three million individuals. The species inhabits seasonally and permanently in northern and southern regions, respectively. This paper provides taxonomic and ecological assessments with an emphasis on morphological measurements, colony size, roosting habitats and national distributional range of Wrinkle-lipped Bat within Vietnam.